Pengaruh efektivitas iklan dan marketing mix terhadap perilaku perpindahan merek - Jajik Puswahono; Suharno Suharno; Saida Zainurossalamia (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2018)
This study aimed to analyze the effect of advertising effectiveness Nu Green Tea to brand switching behavior and the influence of marketing mix on brand switching behavior. The methods used in sampling is using purposive sampling. Data analysis method used is the analysis of Brand Switching Matrix Pattern, and Test Cochran.The results of the analysis indicate that the brand Nu Green Tea has the greatest chance in retaining customers. And all the attributes that were tested all have the same proportion of yes answers based on test Cochran. Then all the attributes are equal consideration in selecting consumer packaged tea beverage.